Efek Transcutaneous Electrical Stimulation (TENS) dan Stretching Terhadap Kasus Cervical Root Syndrome: Case Report - Vina Rosida; Totok Budi Santoso; Taufik Anwar; Farid Rahman (Jurnal Kesehatan dan Fisioterapi, 2022)
Introduction: Cervical root syndrome is a condition caused by irritation or compression of the cervical nerve roots by protrusion of the intervertebral disc with neck pain that radiates to the shoulder, upper arm or forearm, parasthesia and muscle weakness (spasm). Cervical root syndrome (CRS) refers to changes in the cervical spine and surrounding soft tissue with pain as the predominant symptom. Spasm of the muscles can cause pain and limitation of joint motion in the ligament filavum of the segment, pain occurs in the nerve roots that are compressed in a pattern that spreads along the sides of the arm. Objective: Management of physiotherapy in cases of cervical root syndrome (CRS) aims to reduce pain in the neck, so that it can increase the range of motion of the joints and increase functional activity. Methode: The measurement instrument used is the Neck Disabilty Index (NDI). Physiotherapy interventions in cases of cervical root syndrome are given in the form of: Transcutaneous Electrical Stimulation (TENS), and Stretching. Transcutaneous Electrical Stimulation (TENS) is a device used to stimulate analgesia and then sent to the entire surface of the skin to stimulate peripheral nerves through electrode pads. Results: After doing TENS and Stretching on the patient Mr. S has a complaint of feeling pain in the back of the neck when looking to the right accompanied by pain radiating to the point of tingling from the neck to the right hand side. After doing physiotherapy for 3 times using TENS, and stretching, it was found that there was an increase in muscle strength, a decrease in pain, and an increase in the activity of functional abilities. Conclusion: In this article, giving TENS and stretching 3 x per week can reduce pain, increase muscle strength, and increase the ability of functional activities.Keywords: Cervical Root Syndrome, TENS, Stretching